The Reticulospinal Pathway Does Not Increase Its Contribution to the Strength of Contralesional Muscles in Stroke Survivors as Compared to Ipsilesional Side or Healthy Controls - Li, Sheng; Bhadane, Minal; Gao, Fan; Zhou, Ping (Frontiers in Neurology, 2017)
Objective: Startling acoustic stimuli (SAS), via activation of reticulospinal pathways, has shown to increase muscle strength in healthy subjects. We hypothesized that, given reticulospinal hyperexcitability in stroke survivors, SAS could increase muscle strength in stroke survivors. The objective was to quantify the effect of SAS on maximal and submaximal voluntary elbow flexion on the contralesional (impaired) side in stroke survivors as compared to ipsilesional (non-impaired) side and healthy controls. Design: Thirteen hemiparetic stroke survivors and twelve healthy subjects volunteered for this investigation. Acoustic stimulation was given at rest, during ballistic maximal and sustained submaximal isometric elbow contractions using low (80 dB) and high intensity sound (105 dB). The effect of acoustic stimuli was evaluated from EMG and force recordings Results: Prevalence of acoustic startle reflex with shorter latency in the impaired biceps was greater as compared to the response in the non-impaired side of stroke subjects and in healthy subjects. Delivery of SAS resulted in earlier initiation of elbow flexion and greater peak torque in healthy subjects and in stroke subjects with spastic hemiplegia during maximal voluntary elbow flexion tasks. During submaximal elbow flexion tasks, SAS-induced force responses were slightly greater on the impaired side than the non-impaired side. However, no statistically significant difference was found in SAS-induced responses between impaired and non-impaired sides at maximal and submaximal elbow flexion tasks. Conclusion: The findings suggest reticulospinal hyperexcitability in stroke survivors with spastic hemiplegia. The results of similar SAS-induced responses between healthy and stroke subjects indicate that reticulospinal projections via acoustic stimulation are not likely to contribute to muscle strength for stroke survivors to a significant extent.